The effects of the central bank intervention auctions on the foreign exchange futures market: evidence from Brazil - Sung, Gustavo (2021)
This research studied market participants\' behavior to the Central Bank of Brazil (CBB) FX intervention auction. Our objective was to understand how market participants reacted to these macroeconomic events, incorporated new information, and transmitted it to the prices. Based on high-frequency data, it was examined and described a specific trading day of the Brazilian FX futures market, November 26 th, 2019. This strategy allowed us to identify the exact moment the new information arrived and how the market participants reacted. Empirically, we analyzed how those intervention auctions affected the market liquidity and the contribution of bid and ask quotes to price discovery. We used four liquidity indexes and the information share (IS) and the component share (CS) price discovery metrics. The liquidity results showed that the most illiquidity periods occurred at the CBB FX intervention auction periods, mainly the unexpected ones. As for the price discovery, the results indicated that the contribution of the bid (buy-side) and ask (sell-side) quotes to price discovery was asymmetric on that day. With more net buys in the market, the sell-side contributed more to price discovery than the buy-side. In addition to that, the contribution of bid quote and ask quote to price discovery in the Brazilian futures markets varied along the day. The CBB FX selling intervention auctions and, consequently, the negative order flow impacted those changes.